KESALAHAN AFIKSASI DAN PROSES REDUPLIKASI CERPEN KELAS XI BAHASA SERTA RELEVANSINYA DI MA BIDAYATUL HIDAYAH - Bayu Aditya Pratama (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2018)
This research is to find out the affixation errors and short story reduplication process of students class XI Language and relevance in Indonesian language learning at MA Bidayatul Hidayah.This research uses a qualitative method. Data source is 18 short stories Language Class XI student.The data of this study are in the form of affixation and reduplication in the short stories of students of Class XI. Data collection is obtained by documents, see, and record. Data analysis of this study uses Agih method with Direct Element (BUL) technique and matching method to translate into Indonesian. The results this study indicate there are 212 affixation errors. Most writing errors, namely prefixes di- and me (N) -. The reduplication process of 129 students consisted of 86 all repetitions, repetitions in part of 33 repetitions, repetition of affixes of 8 (eight) repetitions, and repetition of phoneme changes of 2 (two) repetitions. The relevance of affixation and reduplication in language learning is an inseparable unity. Affixation and reduplication are studied in class X (ten) in sub-chapter Preparing the Report on Observation Results. The use affixation and reduplication can be found in other study.teaching materials in all subjects are mutually continuous with one another. Keywords: Errors, Affixation, Reduplication, Learning Relevance